2014
DOI: 10.1158/1538-7445.am2014-531
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 531: MiR-199a-5p is a biomarker for and regulator of epithelial-mesenchymal transition in triple-negative breast cancer patients

Abstract: Objectives: Triple-negative breast cancer (TNBC) accounts for 15-20% of all breast cancer, and is characterized by the absence of estrogen receptor, progesterone receptor and human epidermal growth factor receptor. The lack of targeted therapy is a major obstacle for treating against this aggressive subtype, hence the search of specific biomarkers may use as potential diagnostic marker and perhaps a therapeutic target for TNBC. Methods: Plasma samples from patients with TNBC and non-TNBC were recruited for miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Some lncRNAs promote the occurrence and progression of TNBC by regulating their target molecules, showing the characteristics of oncogenes 33 . Other lncRNAs are characterized by tumour suppressor genes and their abnormal expression is closely associated with tumour development or malignant progression 34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some lncRNAs promote the occurrence and progression of TNBC by regulating their target molecules, showing the characteristics of oncogenes 33 . Other lncRNAs are characterized by tumour suppressor genes and their abnormal expression is closely associated with tumour development or malignant progression 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Some lncRNAs promote the occurrence and progression of TNBC by regulating their target molecules, showing the characteristics of oncogenes. 33 Other lncRNAs are characterized by tumour suppressor genes and their abnormal expression is closely associated with tumour development or malignant progression. 34 We found lncRNA PRKCQ-AS1 might interact with miR-361-5p through bioanalysis, and was confirmed that lncRNA PRKCQ-AS1 level was up-regulated in TNBC PTX-resistant cells.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the off-target effects seen with other exogenous RNAs, miRNA therapeutic dosage is often beyond the normal range of endogenous miRNA production [97,98]. The genes that are being targeted by the modified miRNA are directly affected by the dosage of miRNA therapies due to the dose dependence of miRNA-target interactions.…”
Section: What Should Be Done About Dosage?mentioning
confidence: 99%
“…Therapeutic treatments use a variety of methods to obtain effective dosage. One proposed approach to minimizing the therapeutic dosages of individual miRNAs is to use a network of cooperative miRNAs [98]. Vector-based expression systems are another alternative, since they use endogenous promoter sequences to ensure physiologically appropriate and tissue-specific expression levels [22,102].…”
Section: What Should Be Done About Dosage?mentioning
confidence: 99%
“…The downregulation or loss of tumor suppressor miRNA can be overcome by either using ectopic expression of synthetic miRNA mimics [177,178] or utilizing adenovirusassociated transduction vectors of target cells [179][180][181]. MicroRNA analogs are used to restore miRNAs function; this approach is known as miRNA replacement therapy.…”
Section: Mirnas Mimicsmentioning
confidence: 99%